2020
DOI: 10.1111/aos.14397
|View full text |Cite
|
Sign up to set email alerts
|

Retinal oximetry in glaucoma: investigations and findings reviewed

Abstract: Abnormalities of the retinal blood supply have been widely implicated in primary open‐angle glaucoma (POAG). Impaired blood supply to the retina and optic nerve head (ONH) may be a primary pathophysiologic mechanism contributing to POAG (‘vascular hypothesis’). However, the decreased metabolic activity of atrophic tissue is itself known to induce both vascular changes and decreased blood flow due to reduced oxygen demand. Therefore, primary nonvascular factors could potentially induce glaucomatous atrophy, wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 113 publications
1
12
0
Order By: Relevance
“…It is a limitation that 40/111 (36%) of the patients were lost to follow-up after 12 months, but there were no significant differences between the background parameters of these patients and those who were re-examined. Also, there was no significant difference in the oxygen saturations among the BRVO patients with and without glaucoma which has previously been shown to affect retinal oxygen saturation (Shughoury et al 2020). This supports that the findings can be generalized to an unselected population of patients with the studied pattern of retinal vein occlusion at referral and represents a time where recanalization and collateral formation can be expected to have affected the retinal oxygen supply.…”
Section: Discussionsupporting
confidence: 79%
“…It is a limitation that 40/111 (36%) of the patients were lost to follow-up after 12 months, but there were no significant differences between the background parameters of these patients and those who were re-examined. Also, there was no significant difference in the oxygen saturations among the BRVO patients with and without glaucoma which has previously been shown to affect retinal oxygen saturation (Shughoury et al 2020). This supports that the findings can be generalized to an unselected population of patients with the studied pattern of retinal vein occlusion at referral and represents a time where recanalization and collateral formation can be expected to have affected the retinal oxygen supply.…”
Section: Discussionsupporting
confidence: 79%
“…Changes in retinal perfusion can result in the release of reactive oxygen species and impaired vascular autoregulatory mechanisms, and consequently alterations in optic nerve head vascularization. 24 …”
Section: Discussionmentioning
confidence: 99%
“…Advanced glaucoma, increased glaucomatous damage, and poorer visual fields in glaucoma patients have all been associated with increased SvO 2 and reduced AV difference, but there was no significant difference identified in SaO 2 between healthy and glaucoma eyes (Olafsdottir et al 2011(Olafsdottir et al , 2014Ramm et al 2014;Vandewalle et al 2014;Shimazaki et al 2016). Additionally, SaO 2 findings have been mostly consistent in establishing a lack of difference between diseased and healthy eyes (Shughoury et al 2020). However, this review identifies conflicting information regarding SvO 2 , identifying some studies which have not found an increased SvO 2 in glaucomatous patients in both primary open-angle glaucoma and normal-tension glaucoma.…”
Section: Risk Factors and Retinal Oxygenationmentioning
confidence: 98%